The impact of obesity on static and proactive balance and gait patterns in sarcopenic older adults: an analytical cross-sectional investigation - Ferhi,Hamza; Maktouf,Wael (PeerJ, 2023)
Background Obesity is increasingly recognized as a significant factor in the susceptibility of older adults to falls and related injuries. While existing literature has established a connection between obesity and reduced postural stability during stationary stances, the direct implications of obesity on walking dynamics, particularly among the older adults with sarcopenia, are not yet comprehensively understood. Objective Firstly, to investigate the influence of obesity on steady-state and proactive balance, as well as gait characteristics, among older adults with sarcopenic obesity (SO); and secondly, to unearth correlations between anthropometric characteristics and balance and gait parameters in the same demographic. Methods A cohort of 42 participants was categorized into control (CG; n = 22; age = 81.1 ± 4.0 years; BMI = 24.9 ± 0.6 kg/m²) and sarcopenic obese (SOG; n = 20; age = 77.7 ± 2.9 years; BMI = 34.5 ± 3.2 kg/m²) groups based on body mass index (BMI, kg/m²). Participants were assessed for anthropometric data, body mass, fat and lean body mass percentages (%), and BMI. Steady-state balance was gauged using the Romberg Test (ROM). Proactive balance evaluations employed the Functional Reach (FRT) and Timed Up and Go (TUG) tests. The 10-m walking test elucidated spatiotemporal gait metrics, including cadence, speed, stride length, stride time, and specific bilateral spatiotemporal components (stance, swing, 1st and 2nd double support, and single support phases) expressed as percentages of the gait cycle. Results The time taken to complete the TUG and ROM tests was significantly shorter in the CG compared to the SOG (p < 0.05). In contrast, the FRT revealed a shorter distance achieved in the SOG compared to the CG (p < 0.05). The CG exhibited a higher gait speed compared to the SOG (p < 0.05), with shorter stride and step lengths observed in the SOG compared to the CG (p < 0.05). Regarding gait cycle phases, the support phase was longer, and the swing phase was shorter in the SOG compared to the CG group (p < 0.05). LBM (%) showed the strongest positive correlation with the ROM (r = 0.77, p < 0.001), gait speed (r = 0.85, p < 0.001), TUG (r = −0.80, p < 0.001) and FRT (r = 0.74, p < 0.001). Conclusion Obesity induces added complexities for older adults with sarcopenia, particularly during the regulation of steady-state and proactive balance and gait. The percentage of lean body mass has emerged as a crucial determinant, highlighting a significant impact of reduced muscle mass on the observed alterations in static postural control and gait among older adults with SO.
Keywords: Sarcopenia; Obesity; Walking; Proactive balance; Lean body mass; Fat body mass